2022
DOI: 10.1038/s41467-022-34962-7
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-bonded shape memory polymers

Abstract: Halogen bonding (XB), a non-covalent interaction between an electron-deficient halogen atom and a Lewis base, is widely adopted in organic synthesis and supramolecular crystal engineering. However, the roadmap towards materials applications is hindered by the challenges in harnessing this relatively weak intermolecular interaction to devise human-commanded stimuli-responsive soft materials. Here, we report a liquid crystalline network comprising permanent covalent crosslinks and dynamic halogen bond crosslinks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 84 publications
1
35
0
Order By: Relevance
“…1−3 The incorporation of halogen bond donors into polymers has led to the development of topochemical polymerization, molecularly-imprinted polymers, functional-/stimuli-responsive polymeric materials, 1,2,4 and, most recently, shape-memory polymers. 5 A main advantage of halogen bonding is its highly directional nature, owing to its electronic origin as a σ−hole interaction (i.e., the tightly confined electropositive region along the axis of the halogen bond donor's R−X bond), 6 which has found great utility in the construction of a variety of supramolecular architectures. 7−14 The epitome of halogen bonding is the linear halogen(I) (also termed halonium) complexes, 15,16 which comprise a halenium ion (X + ; X = Cl, Br, and I) and a pair of stabilizing Lewis bases (L; commonly nitrogen-based aromatic ligands such as pyridine), [L−X−L] + .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−3 The incorporation of halogen bond donors into polymers has led to the development of topochemical polymerization, molecularly-imprinted polymers, functional-/stimuli-responsive polymeric materials, 1,2,4 and, most recently, shape-memory polymers. 5 A main advantage of halogen bonding is its highly directional nature, owing to its electronic origin as a σ−hole interaction (i.e., the tightly confined electropositive region along the axis of the halogen bond donor's R−X bond), 6 which has found great utility in the construction of a variety of supramolecular architectures. 7−14 The epitome of halogen bonding is the linear halogen(I) (also termed halonium) complexes, 15,16 which comprise a halenium ion (X + ; X = Cl, Br, and I) and a pair of stabilizing Lewis bases (L; commonly nitrogen-based aromatic ligands such as pyridine), [L−X−L] + .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Halogen bonding enjoys being one of the most studied types of intermolecular interactions after hydrogen bonding, and as such has been deftly employed to construct a myriad of magnetic, porous, phosphorescent, and liquid-crystalline materials toward applications such as biomolecular engineering, chemical separations, and ion-pair recognition. The incorporation of halogen bond donors into polymers has led to the development of topochemical polymerization, molecularly-imprinted polymers, functional-/stimuli-responsive polymeric materials, ,, and, most recently, shape-memory polymers . A main advantage of halogen bonding is its highly directional nature, owing to its electronic origin as a σ–hole interaction ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The number of investigations concerning halogen bonding can be compared with the solar‐cells “big boom”. A lot of recent research data can be easily found in the literature [13–18] . In Russia such studies are actively being developed by the leading research groups of Prof. V. Yu.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of recent research data can be easily found in the literature. [13][14][15][16][17][18] In Russia such studies are actively being developed by the leading research groups of Prof. V. Yu. Kukushkin and Prof. S. A. Adonin.…”
Section: Introductionmentioning
confidence: 99%
“…17 Guo has pointed out the necessity of halogen bonds for the shape memory effect in organic polymers. 18…”
Section: Introductionmentioning
confidence: 99%